ANALISIS INDOOR AIR QUALITY TERHADAP GEJALA SICK BUILDING SYNDROME PADA PEKERJA DI PT X TAHUN 2023 - Alya Diah Ullhaque (2024)
Poor indoor air quality can harm human health. A closed indoor work environment and an inadequate ventilation system can increase the risk of sick building syndrome symptoms. This study aims to analyze the most significant risk factors with symptoms of sick building syndrome in workers at PT X. The study used a cross-sectional study design and the data was processed with the chi-square test and multiple logistic regression tests with a sample of all production area workers at PT X. A total of 91 workers included in this study. Carbon monoxide, temperature, humidity, PM10 and formaldehyde were measured using a particle counter and wind speed was measured using an anemometer. Measurements were taken at 17 different points. The results showed that 85 out of 91 workers (93.4%) experienced symptoms of sick building syndrome. There is a relationship between temperature (p-value=0.013) and wind speed (p-value=0.031) symptoms of sick building syndrome. The most dominant variable is the formaldehyde (POR=0.457). It is concluded that the variables associated with symptoms of sick building syndrome are temperature and wind speed, with formaldehyde being the most dominant. The company is advised to monitor indoor air quality regularly and improve the ventilation system at the production area.